Perovskite-Induced Ultrasensitive and Highly Stable Humidity Sensor Systems Prepared by Aerosol Deposition at Room Temperature - Cho, Myung Yeon; Kim, Sunghoon; Kim, Ik Soo; Kim, Eun Seong; Wang, Zhi Ji; Kim, Nam Young; Kim, Sang Wook; Oh, Jong Min (Advanced Functional Materials, 2020)
A new capacitive-type humidity sensor is proposed using novel materials and fabrication process for practical applications in sensitive environments and cost-effective functional devices that require ultrasensing performances. Metal halide perovskites (CsPbBr3 and CsPb2Br5) combined with diverse ceramics (Al2O3, TiO2, and BaTiO3) are selected as sensing materials for the first time, and nanocomposite powders are deposited by aerosol deposition (AD) process. A state-of-the-art CsPb2Br5/BaTiO3 nanocomposite humidity sensor prepared by AD process exhibits a significant increase in humidity sensing compared with CsPbBr3/Al2O3 and CsPbBr3/TiO2 sensors. An outstanding humidity sensitivity (21426 pF RH%−1) with superior linearity (0.991), fast response/recovery time (5 s), low hysteresis of 1.7%, and excellent stability in a wide range of relative humidity is obtained owing to a highly porous structure, effective charge separation, and water-resistant characteristics of CsPb2Br5. Notably, this unprecedented result is obtained via a simple one-step AD process within a few minutes at room temperature without any auxiliary treatment. The synergetic combination of AD technique and perovskite-based nanocomposite can be potentially applied toward the development of multifunctional sensing devices.
Keywords: Aerosol deposition; Fabrication process; Functional devices; Halide perovskites; Humidity sensing; Humidity sensitivity; Nano-composite powders; Porous structures; aerosol deposition; humidity sensitivity; humidity sensors; perovskite/ceramic nanocomposites; stability